Cumulative sum learning curve analysis of tubularized incised plate repair for hypospadias: a study of a single surgeon with a single surgical procedure - Li, Jiaqiang; Zhang, Jiaqian; Diao, Hongwang; He, Zhuoyuan; Li, Shoulin; Yin, Jianchun (Frontiers in Pediatrics, 2024)
To ascertain the quantity of instances by which a single surgeon achieves competency and proficiency in using tubularized incised plate (TIP) technique for the repair of distal and mid-shaft hypospadias using the cumulative sum (CUSUM) analysis.We retrospectively evaluated patients with distal and mid-shaft hypospadias who were treated by a single surgeon between 2015 and 2021, using a single primary TIP technique with a de-epithelialized Byars flap. Data including type of hypospadias, age at surgery, curvature, operation time (OT), length of the reconstructed urethra, and postoperative outcomes were collected and assessed.CUSUM was used to assess the trends in OT and complication rate (CR) in order to generate the learning curve. The evolution of OT and CR can be divided into three phases: learning, competence, and proficiency.Results: CUSUM identified three phases in the learning curves of all TIP repairs. The median OT decreased from 135 min (interquartile range [IQR]=125-155) to 92 min (IQR=80-100) (P<0.001), CR decreased from 28 (28%) to 8 (5.3%) (P<0.001), and reoperations decreased from 15 (15.2%) to 4 (2.6%) (P<0.001). According to the CUSUM learning curve, technical competency plateaued after the 99th case, and both OT and CR entered a significantly declining proficiency phase after the 231st case.Further, when the neourethral length exceeded the total average, total complications, urethrocutaneous fistula, and reoperations increased (P=0.013, P=0.006, and P=0.028, respectively).Our study suggests that surgeons performing TIP repair may reach technical competency and achieve proficiency after operating on 99 231 cases, respectively. Moreover, the longer the neourethral length, the higher is the CR.